Do Consumers Benefit from Concentration in the New Economy? A Review of Google's Mergers, Acquisitions, and Arrangements - Patrick Frank Ernst Beschorner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Within the last three years, Google has acquired YouTube and DoubleClick and has attempted to control part of Yahoo!'s search advertising business. Two of the deals have not raised antitrust concerns by competition authorities. I review these deals with a focus on consumer welfare. Consumers are affected by being on one side of a multisided platform. Provided that better matches of search ads are beneficial, I demonstrate that the mergers may have positive effects for consumers through better matches between users and search ads. However, this does not substitute an in-depth antitrust assessment of the deals.
Keywords: K21; L42; M37; L41; 330; merger control; multisided platforms; screening mechanism; Suchmaschine; Online-Werbung; Fusion; Wirtschaftskonzentration; New Economy; Konsumentenrente; Informationsverhalten; Matching; Theorie; USA; Google Inc. <Mountain View; Calif.>